lambda - statistical convergence in fuzzy normed linear spaces - Turkmen, Muhammed Recai; Çınar, Muhammed (IOS PRESS, 2018)
In this paper, we have introduced lambda - statistical convergence and condition of being lambda - statistical Cauchy of real number sequences in fuzzy normed linear spaces. At the same time, in fuzzy normed spaces, we have introduced the concept of (V , lambda)summability and (C, 1) summability, and then, we have studied the relation between these concepts and lambda-statistical convergence.
WOS: 000436432400051
Keywords: lambda - statistical convergence; fuzzy normed linear space; summability